1996
DOI: 10.1152/ajpregu.1996.271.6.r1729
|View full text |Cite
|
Sign up to set email alerts
|

Beta 3-adrenoceptor in guinea pig brown and white adipocytes: low expression and lack of function

Abstract: In the guinea pig, cold acclimation induced a conversion of unilocular to multilocular adipocytes in interscapular (IS) and retroperitoneal (RP) fat depots but not in the epididymal (EP) fat pad. The conversion was associated with an increase in mitochondriogenesis and the appearance of the uncoupling protein. The maximal lipolytic responses to norepinephrine and dibutyryl adenosine 3',5'-cyclic monophosphate were decreased in IS cells, unchanged in RP cells, and increased in EP cells, suggesting a site-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Head width, crown rump length, abdominal circumference, body weight/crown rump length, and ponderal index (body weight/crown rump length 3 ) were reduced in fetuses of feedrestricted mothers at day 60 of gestation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Head width, crown rump length, abdominal circumference, body weight/crown rump length, and ponderal index (body weight/crown rump length 3 ) were reduced in fetuses of feedrestricted mothers at day 60 of gestation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…As in humans, adipose depots containing BAT in the guinea pig are transformed after the neonatal period into tissues with the characteristics of white adipose tissue (9,21). Cold acclimation can reactivate BAT in adult guinea pigs (3,21). Uncoupling protein-1 mRNA is detected in adipose tissue in adult humans, suggesting that small numbers of brown adipocytes are present (9,10,20,35).…”
Section: Discussionmentioning
confidence: 99%
“…Since human adipocytes are also devoid of functional β 3 -ARs (8,24,32), this can be the major reason for the low number of phase II or III developments of orally given β 3 -AR agonists for the indications of obesity or diabetes (29). Another resemblance between guinea pig and human adipocytes is that, besides their poor β 3 -adrenergic receptivity, both exhibit poor responsiveness to insulin, at least regarding the stimulation of glucose upake (4,23). This stricking association between low β 3 -adrenergic and low insulin responsiveness has been already noted in guinea pig brown adipocytes by Himms-Hagen and coworkers (20).…”
Section: Discussionmentioning
confidence: 99%
“…These controversial observations on the effects of β 3 -AR agonists on glucose utilisation prompted us to verify in two models whether sustained β 3 -adrenergic activation was modifying glucose transport capacity in adipocytes. The three β-AR subtypes, including the β 3 -receptor are present on rat adipocytes (16) while only β 1 -, and β 2 -ARs are functional in guinea pig adipocytes (4,8,10). Since we have reported that the β 3 -AR agonist CL 316243 induces adipose tissue remodeling in rat but not in guinea pig (14) we aimed to compare in rat and guinea pig adipocytes the influence of chronic CLtreatment on glucose transport activity and insulin responsiveness.…”
mentioning
confidence: 99%
“…However, white fat cells from primates -including humans -exhibit only weak activation of lipolysis in response to β 3 -AR agonists while they respond to β 1 -or β 2 -AR agonists (Langin et al 1991;Bousquet-Mélou et al 1994;Tavernier et al 1996;Umekawa et al 1996). Guinea-pig adipocytes are also unresponsive to β 3 -AR stimulation Atgié et al 1996) while dog fat cells share equivalent β 1 -, β 2 -or β 3 -adrenergic responsiveness (Galitzky et al 1993b;1995). We have reported already that octopamine stimulates lipolysis in canine adipocytes in a manner resistant to the blockade by β 1 -or β 2 -selective antagonists, suggesting activation of atypical β-ARs (Galitzky et al 1993a).…”
Section: Introductionmentioning
confidence: 99%